Cost-effective handling of digital medical images in the telemedicine environment - Choong, Miew Keen; Logeswaran, Rajasvaran; Bister, Michel (ELSEVIER IRELAND LTD, 2007)
Background: This paper concentrates on strategies for less costly handling of medical images. Aspects of digitization using conventional digital cameras, lossy compression with good diagnostic quality, and visualization through less costly monitors are discussed.